Reformasi Praktik Pengawasan di Sekolah Dasar dalam Memperbaiki Mutu Pendidikan pada Era Otonomi Daerah - Dadang Suhardan (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: The basic problem of monitoring practices in elementary school is intention and socialization of good competition. This study tried to describe monitoring concepts based on quality process reformation and learning outcomes orientation. The research location is in the State Elementary School Kecamatan Lengkong, Bandung City. The data were collected by observation, in-depth interview, filling list, documentation study, and audio and tape recorder. The collected data were analyzed by members check, triangulation, and laboratory analysis. The result found that a principal stated 35 % to 40 % of the all times should be used for improving learning quality. The rest of the principal time can be allocated to leadership tasks. The result can be seen as a change of supervision function.